Nickel- and Fe3+-rich oxy-dravite from the Artana Mn prospect, Apuan Alps (Tuscany, Italy) - Mauro,D.; Biagioni,C.; Hålenius,U.; Skogby,H.; Dottorini,V.; Bosi,F. (Journal of Geosciences, 2022)
Nickel- and Fe3+-rich oxy-dravite was identified on a specimen collected in the Artana Mn prospect, Carrara, Apuan Alps, Tuscany, Italy. Oxy-dravite occurs as brownish-orange prismatic crystals, up to 0.3 mm in length, associated with quartz, carbonates, and hematite. Electron microprobe analysis gave (in wt. % - average of 7 spot analyses): SiO2 35.81, TiO2 0.41, B2O3(calc) 10.38, Al2O3 29.36, V2O3 0.78, Cr2O3 0.09, Fe2O3 3.32, FeO 0.33, MgO 8.04, CaO 0.39, MnO 0.34, NiO 3.46, ZnO 0.40, Na2O 2.84, F 0.29, H2O(calc) 3.00, O = F -0.12, total 99.12. The Fe3+/Fetot ratio was calculated based on optical absorption spectroscopy. The empirical ordered formula of the studied sample is (with rounding errors) X(Na0.92Ca0.07□0.01)Σ1.00 Y(Mg2.01Ni2+0.47Fe3+0.33Ti0.05 Mn2+0.05Fe2+0.05Zn0.05)Σ3.00 Z(Al5.80V0.10Cr0.01Fe3+0.09)Σ6.00 Si6O18(BO3)3 V(OH)3W[O0.50(OH)0.35F0.15]Σ1.00. This is an intermediate member of the dravite-oxy-dravite series. In naming it, the prefix oxy- was preferred since WO is very close to being larger than 0.5 atoms per formula unit. Infrared spectroscopy revealed the occurrence of significant amounts of W(OH), and allowed to propose of specific short-range arrangements around the O(1) and O(3) sites. Unit-cell parameters are a = 15.9349(11), c = 7.2038(5) Å, V = 1584.1(2) Å3, space group R3m. The crystal structure was refined by single-crystal X-ray diffraction data to R1 = 0.0146 on the basis of 1138 unique reflections with Fo > 4σ(Fo) and 94 refined parameters. The optimized crystal-chemical formula is X(Na0.92Ca0.07□0.01)Σ1.00 Y(Mg1.21Al0.80Ni2+0.47Fe3+0.26 Ti0.05Mn2+0.05Zn0.05V0.10Cr0.01)Σ3.00 Z(Al5.00Mg0.80Fe3+0.16Fe2+0.05)Σ6.00 Si6O18(BO3)3O(3)(OH)3O(1) [O0.50(OH)0.35F0.15]Σ1.00. Nickel is ordered at the Y site, in agreement with results obtained on synthetic tourmalines. Oxy-dravite is likely the result of the metamorphic recrystallization of Mn-rich layers at the top of the Liassic carbonates belonging to the Marble Formation of the Apuan Alps Metamorphic Complex.
Keywords: tourmaline supergroup; oxy-dravite; nickel; crystal structure; Apuan Alps; Italy